Rib stress injuries among female national collegiate athletic association rowers: a prospective epidemiological study - Madison, C. A.; Harter, R. A.; Pickerill, M. L.; Housman, J. M. (International Journal of Athletic Therapy & Training, 2022)
Rib stress injuries (RSIs) are debilitating injuries that competitive rowers often sustain during their careers, losing up to 10 weeks of training per year. Minimal research exists on RSIs and associated risk factors among National Collegiate Athletic Association women`s open-weight rowers. The purpose of this study was to determine the prevalence of RSIs and assess injury risk factors in intercollegiate female rowers. A prospective 14-week in-season injury surveillance was conducted via online surveys to collect demographic information, identify intrinsic and extrinsic risk factors, and document RSIs and other rowing-related injuries. During one National Collegiate Athletic Association season, 26% of our participants reported a rib cage injury, with six of these injuries identified as potential RSIs. Estimated prevalence for rib cage injuries is 6-33% in National Collegiate Athletic Association women`s rowing teams. RSI reporting and recognition was followed by aggressive clinical management in the population sampled, suggesting the need for larger scale epidemiological studies to determine the true prevalence, severity, and typical clinical course of these injuries.